Results of rhinoplasties of the nasal tip in Cienfuegos - Bernardo Félix Canto Vidal; Angel Viera Docil (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
Background: the rhinoplasty of the nasal tip is one of the most difficult and challenging plastic surgeries the surgeon dedicated to the nasal deformities faces. Objective: exposing the results of the rhinoplasty accomplished to patients with nasal deformities. Methods: a descriptive study of results obtained in 145 patients who had a surgery to correct nasal deformities. They were attended at Dr. Gustavo Aldereguía Lima University General Hospital of Cienfuegos, in a period of 10 years. Results: in 56 patients surgery was headed for embracing the nasal tip; in 45 patients to the rotation of the nasal tip; and in 44 patients to the projection of the nasal tip. The technique of the banner with graft of cartilage of the septum and the ear was used. Conclusion: in the analyzed period, the rhinoplasty accomplished in the province of Cienfuegos had satisfactory results, because the patient's expectations were satisfied with a reduction of the costs of risks for them due to the use of local anesthesia.